Evaluation of Land Suitability for Transmigration Location in SP4 Hote, East Seram Regency - Riry, Roberth Berthy (Universitas Pattimura, 2023)
The transmigration program is a government policy that accelerates development in remote areas. Selecting the right transmigration locations is crucial for the success of this program. Land suitability is a key factor in determining the optimal location. This study assesses land suitability for transmigration locations by considering the land's physical conditions, the local community's socio-economic conditions, and the applicable policies. The research findings indicate that land suitability in SP4 Hote is highly dependent on physical land conditions, such as soil fertility, water availability, topography, and climate. Socio-economic factors such as accessibility, employment opportunities, and economic sustainability are also important. The land area in SP4 Hote is 725 hectares, including residential plots, farming areas, public facilities, cemeteries, test farms/seed farms, roads, and conservation areas. The composition of local and non-local transmigrants in Hote is 40% and 60%, respectively. The commodities that can be developed in this location include food crops, fruits, and perennial crops such as rubber and oil palm